Capacitor-Voltage Feedforward With Full Delay Compensation to Improve Weak Grids Adaptability of LCL-Filtered Grid-Connected Converters for Distributed Generation Systems - Li, Xiaoqiang; Fang, Jingyang; Tang, Yi; Wu, Xiaojie; Geng, Yiwen (IEEE transactions on power electronics, 2018)
LCL-filtered grid-connected converters are widely used for distributed generation systems. However, the current regulation of such converters is susceptible to weak grid conditions, e.g., grid impedance variation and background harmonics. Paralleling multiple harmonic compensators (HCs) is a commonly used method to suppress the current distortion caused by grid background harmonics, but the control bandwidth should be wide enough to ensure system stability. In order to enhance the adaptability of LCL-filtered grid-connected converters under weak grid operation, this paper proposes an improved capacitorvoltage-feedforward control with full delay compensation. When used with converter-side current feedback, the proposed control can keep system low-frequency characteristic independent of grid impedance and provide a high-harmonic rejection capability without using additional HCs. Moreover, it completely avoids the design constraints of an LCL filter, i.e., ω τ <; ω 8 /6 is required for singleloop converter-side current control. Therefore, a higher resonant frequency can be designed to achieve a wider control bandwidth and to lower the current distortion caused by the paralleled filter capacitor branch. Experimental results are finally presented to verify the proposed control, which are also in good agreement with theoretical analysis.